Genealogy of the Twining family, descendants of William Twining, Sr. Who came from Wales, or England, and died at Eastham, Massachusetts, 1659. With information of other Twinings in Great Britain and America. - Twining, Thomas J. (Thomas Jefferson), 1851- (Chicago, Pub. for the author, 1890)
Family history of William Twining (approximately 1594-1659) born in England, migrated to the United States between 1630 and 1640.
Mode of access: Internet.
Keywords: Twining family; Registers of births, etc. -- United States; Great Britain -- Genealogy; Massachusetts -- Genealogy; United States -- Genealogy; Histoires familiales; Family histories; Family histories; Genealogy